Bioprocessing for biofuel production strategies to improve process parameters - Srivastava, Neha 1981-; Srivastava, Manish 1973-; Mishra, P.K; Gupta, Vijai Kumar 1981- (Clean energy production technologies, 2021)
Converting biomass to biofuels involves hydrolyzing cellulose to sugars using cost-intensive commercial enzymes - an expensive step that makes large-scale production economically non-viable. As such, there is a need for low-cost bioprocessing. This book critically evaluates the available bioprocessing technologies for various biofuels, and presents the latest research in the field. It also highlights the recent developments, current challenges and viable alternative approaches to reduce the overall cost of producing biofuels